Does Oral Endotoxin Contribute to Systemic Inflammation? - Zenobia, Camille; Darveau, Richard P. (Frontiers in Oral Health, 2022)
The oral microbiome, with a unique emphasis on Porphyromonas gingivalis has been associated with a constellation of inflammatory diseases such as cardiovascular disease, Rheumatoid Arthritis, Alzheimer's Disease, Type II Diabetes, and Non-Alcoholic Associated Fatty Liver Disease. Periodontal disease has also been shown to induce ‘leaky gut’ leading to Metabolic Endotoxemia. Several recent studies investigating the habitants of the blood microbiome have found the majority of species appear to be derived from oral and skin bacterial communities in otherwise healthy individuals. Many of the same pathologies associated with perturbations of oral health, such as cardiovascular disease, show alterations to the composition of the blood microbiome as well as circulating neutrophil phenotypes. Gingival inflammation is associated with activated blood neutrophil phenotypes that can exacerbate a distal inflammatory insult which may explain the connection between oral and systemic inflammatory conditions. While in the oral cavity, neutrophils encounter oral microbes that are adept in manipulating neutrophil activity which can re-enter the vasculature thereafter. Endotoxin from oral microbes can differ significantly depending on bacterial community and state of oral health to alter cellular LPS tolerance mechanisms which may contribute to the primed neutrophil phenotype seen in periodontal disease and provide a mechanism by which the oral-microbes can affect systemic health outcomes. This review synthesizes the studies between inflammatory diseases and oral health with emphasis on microbiome and corresponding lipopolysaccharides in immune tolerance and activation.